2003
DOI: 10.1897/02-503
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of toxicity of zinc for soil microbial processes between laboratory‐contamined and polluted field soils

Abstract: Soil microbial processes are readily disturbed by added zinc (Zn) in laboratory ecotoxicity tests. This study compares Zn toxicity between freshly spiked soils and soils that have been contaminated with Zn in the field. Soils were sampled in three transects (< 80 m) toward galvanized electricity transmission towers (pylons). The soil total Zn concentrations gradually increased in each transect from background values (25-82 mg Zn/kg) to elevated Zn concentrations near the pylon (226-595 mg Zn/kg). Soil samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 26 publications
3
48
0
Order By: Relevance
“…There exist bioassay-derived ecotoxicity/ bioavailability databases for a large number of soil organisms, largely based on the use of soluble metal salts and often with no soil matrix effects. Clearly such measurements overestimate many-fold the risks from soil TEs when compared with field situations [203,204,215]. There is an obvious need to revisit such ecotoxicity database for necessary corrections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There exist bioassay-derived ecotoxicity/ bioavailability databases for a large number of soil organisms, largely based on the use of soluble metal salts and often with no soil matrix effects. Clearly such measurements overestimate many-fold the risks from soil TEs when compared with field situations [203,204,215]. There is an obvious need to revisit such ecotoxicity database for necessary corrections.…”
Section: Discussionmentioning
confidence: 99%
“…Often such studies have been carried out using soils freshly spiked with soluble metal salts. This does not represent real contamination situations, and like plants, such approaches overestimate TE bioavailability to soil organisms (for example [203,204]). Short-term bioassays and those involving freshly spiked soils therefore may not help in assessing the risk that TEs pose to soil organisms under real field situations.…”
Section: Bioassays Biosensors and Bioavailabilitymentioning
confidence: 99%
“…Regression models are present in Table 3. Dai et al (2004) and Smolders et al (2003), the effects of other metals were not significant.…”
Section: Effects Of Metals On Pnr and Nmin Responses Normalized By Ommentioning
confidence: 79%
“…For example, Oorts et al (2006) indicated that in field-contaminated soil, toxicity thresholds of Cu for nitrifying microorganisms are higher than in metal-spiked soils. Similarly, the study of Smolders et al (2003) reveals a discrepancy in Zn toxicity to microbial responses between metal-spiked and fieldcontaminated soils.…”
Section: Introductionmentioning
confidence: 99%
“…The bioavailability of pollutants in comparable soil types polluted in the field or spiked in the lab is different (Smolders et al, 2003). Soil characteristics, e.g.…”
Section: Earthworm Biomarker Relevance For Soil Pollution Monitoring mentioning
confidence: 99%